Diagrama de Voronoi: uma exploração nas distâncias Euclidiana e do Táxi - Santos, Paula Roberta Scaburi dos (2016)
The objective of the present work is to explore the concept of Voronoi diagram considering Euclidean distance and Taxi-distance. After a brief introduction, the second chapter begins with an informal definition of Voronoi diagram considering Euclidean distance and brings a sequence for the construction of the diagram in the plane for two, three and four points, using the concept of perpendicular bisector. After this sequence, a formal definition is introduced and some properties and theoretical results about the diagram are presented. In the third chapter we consider the ideia of Voronoi diagram in the Taxi-distance. After defining the taxi-distance, we explore some related geometric locus as circunference and bisectors, highlighting the differences and similarities with the Euclidean distances. Some examples for three- and four-point diagrams are presented. The fourth chapter considers an idea for the representation of the regions of influence of the Voronoi diagram in the Euclidean distance and the taxi-distance, using GeoGebra. The construction presented involve the concept of circumference and bisector in each metric and its relation with the regions of influence of the Voronoi diagram. Finally, the fifth chapter presents some suggestions of activities for High School students related to the Voronoi diagram, involving concepts of Analytical and Plane Geometry.